Regenerative braking model for electric vehicles with modified super-twisting sliding mode control - Ghazali, Anith Khairunnisa (2021)
As global warming comes and the prices of fuel keep rising, the clean and environmental friendly features of electric vehicles are increasingly focused. The electric vehicle is ideally compatible with the existing situation due to its efficiency compared to the Internal Combustion Engine (ICE). For full electric vehicles, the battery is the only source of energy, and the battery faces issues such as longer charging period. In general, Battery Electric Vehicle (BEV) has limited driving range due to battery capacity storage. The regenerative braking system (RBS) became important for electric vehicles that could allow motor vehicles function as a generator and alternator for the recovery process of kinetic energy during a braking event. During regenerative braking, the kinetic energy produced by the engine during deceleration and the energy needs to be recycled to extend driving range. The energy will be transmitted to charge the battery or store it in the energy storage. If the braking force distribution is not adequately regulated, the controller might fail to generate the necessary braking torque. In reality, the battery pack will cause harm due to overcharging induced by uncontrolled recovery. Appropriate braking system are required to be established in order to optimise the energy transferred during the regenerative braking process. The presence of classical regenerative braking is to optimise the regeneration of kinetic energy by reconciling regenerative technology with braking efficiency and vehicle behaviour. However, the existing result is insufficient where only 1056.6 kJ per cycle for the Urban Dynamometer Driving Schedule (UDDS) and 4599 kJ per cycle for New European Driving Cycle (NEDC). This research introduced new topology of Integrated Regenerative Braking Force Distribution (IBFD) for optimum braking and vehicle stability by combining average speed distribution of the braking force with National Renewable Energy Laboratory (NREL) braking design. The average speed level for the urban driving cycle in Malaysia is 31.89 km/h. The average braking force is used to optimise the default braking distribution mechanism. This research verify conventional Sliding Mode Control Super-Twisting (SMCST) controller because it is useful due to it robustness against the disturbances and uncertainties. Even though the conventional SMCST controller confirms the stability, nevertheless it gives unsatisfied performance to obtain the desired State of Charge (SoC). Thus, the modified Sliding Mode Control Super-Twisting with hybrid fuzzy-gain scheduling optimisation component was proposed. The proportional gain was added to the switching control for faster response to the desired sliding surface. The modified SMCST is pairing with IBFD. Based on the results for NEDC, driving cycle using modified SMCST with IBFD braking, the energy transmitted is 600 kJ more than NREL, average motor efficiency increase to 0.85, overall efficiency 2.799 and the SoC is 0.899. The slip ratio output at 32 km/h deceleration is -0.19 that proved the stability of this topology. The proposed methodologies successfully integrate the regenerative and friction braking forces to achieve the control goal.